Computational fluid dynamics analysis of an injection mixer for CNG engines simulation - Mohsin, Rahmat; Yaacob, Zulkefli; Chang, Yvonne (Penerbit UTM Press, 2008)
The poor mixing in gaseous injection mixers is one of the culprits for unsatisfactory engine performance and lethal exhaust emissions. Thus, effect of injection frequency on the mixing in Throttle Body Injection Mixer (TBIM) for a CNG motorcycle was studied in this work through Computational Fluid Dynamics (CFD) simulation. Injection frequencies of 1, 2, 4, 5 and 7 injections per engine cycle had been investigated using the RNG Îºâˆ’Îµ turbulent model. CFD results revealed a significant effect of various injection frequencies on the hydrodynamics of air and fuel in TBIM. It was found that the injection frequency of 4 injections per engine cycle was the most optimum one throughout the case studies.